Frequency and co-colonization of vancomycin-resistant Enterococci and Candida in ICU-hospitalized children. (May 2021) - Shirvani, F.; Behzad, A.; Abdollahi, N.; Mohkam, M.; Sharifian, M.; Esfandiar, N.; Fallah, F.
Abstract: In the time span between January 2018 and September 2020, 205 patients were enrolled in a prospective cohort study at Mofid Children's Hospital. Demographic information and clinical data on all the participating children were collected and rectal swabs were performed for the sampling method. All samples were analysed so as to identify the presence of Enterococcus and Candida colonization by the use of conventional biochemical tests. Resistance to vancomycin in Enterococcus isolates was phenotypically identified using an E-test kit and MIC value, interpreted according to the CLSI criteria. The presence of vanA and vanB genes, which encode the resistance to vancomycin, was screened by PCR assay. Candida species were detected in 21.5% of rectal swab samples. Candida glabrata (56.8%) and Candida albicans (43.2%) were the only Candida species detected. Enterococcus species were detected in 29.3% of rectal swab samples. Out of 60 Enterococcus isolates, 33 (55%) were resistant to vancomycin. Moreover, vanA was detected in 84.8% and vanB was detected in 3% of the 33 vancomycin-resistant Enterococcus isolates. Enterococcus and Candida species were frequently detected in the <1 year and 1–3 years age groups, respectively. Central venous access catheter and brain tumour were the main reasons for hospital admissions, 32.2% and 20.1% of total admissions, respectively. Furthermore, it must be noted that the most frequent underlying medical conditions in participating patients were esophageal atresia and hydrocephalus. The results of the present study demonstrated the necessity of determining the susceptibility of Enterococcus isolates to vancomycin before prescribing antibiotics.